Nineteenth-century religion, literature and society.
1 online resource
Keywords: This four-volume historical resource provides new opportunities for investigating the relationship between religion, literature and society in Britain and its imperial territories by making accessible a diverse selection of harder-to-find primary sources. These include religious fiction, poetry, essays, memoirs, sermons, travel writing, religious ephemera, unpublished notebooks and pamphlet literature. Spanning the long nineteenth century (c.1789-1914), the resource departs from older models of the Victorian crisis of faith' in order to open up new ways of conceptualising religion. This second volume is calledMission and Reform' and itconsiders the social and political importance of religious faith and practice as expressed through foreign and domestic mission and philanthropic and political movements at home and abroad.